CD4+ T cell proliferative responses to PPD and CFP-10 associate with recent M. tuberculosis infection. (July 2020) - Borgström, Emilie Wahren; Fröberg, Gabrielle; Correia-Neves, Margarida; Atterfelt, Fredrik Bosdotter; Bellbrant, Jan; Szulkin, Robert; Chryssanthou, Erja; Ängeby, Kristian; Tecleab, Teghesti; Ruhwald, Morten; Andersen, Peter; Källenius, Gunilla; et al.
Abstract: Interferon-γ release assays cannot differentiate latent from active tuberculosis (TB), nor identify the recently infected with increased risk of active disease. The objective of this study was to identify biomarkers of recent infection following exposure to tuberculosis, to increase the positive predictive value for incipient TB. Contacts to patients with pulmonary TB were tested repeatedly with interferon-γ release assays and flow-cytometry. Proliferative CD4 + T cell responses to purified protein derivative (PPD) and 11 M. tuberculosis antigens were analysed. The individual probability of recent and remote infection was estimated using clinical data in a novel mathematical model and compared with CD4 + responses in a prediction model. The most specific prediction of recent infection was high CD4 + proliferative responses to CFP-10 and PPD and a low CD4 + response to ESAT-6. CD4 + proliferative responses to Rec85a, Rec85b and Rv1284 were also observed in recent infection, but did not reach significance in the prediction model. Conclusions: High CD4 + proliferative responses to CFP-10 and PPD and a low response to ESAT-6 may be used as biomarkers to improve positive predictive values for recent LTBI and thus, increased risk of incipient TB. Rec85a, Rec85b and Rv1284 are also of interest to study further in this context.